Spatial attractiveness towards industrial placement: a parametric index based on spatial-economic territorial exposure metrics - Altafini, Diego; Cutini, Valerio (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The asymmetrical process of industrial development tends to increase regional disparities and result in different patterns of territorial exposure: the amount of support given to activities placed within industrial agglomerates. Spatial Attractiveness towards industrial placement tends to follow such patterns, as places with lower exposure tend to be more attractive, providing more support to productive activities. Spatial models based in economic methods have issues in precising the nature of Spatial Attractiveness disparities, as their interpretation of space as an abstracted parameter, provides insufficient locational precision to demonstrate these patterns and how those are dependent on relations between production, territorial endowments, and industrial agglomerates’ internal organization. Novel spatial-economic models ought to consider and incorporate spatial units reflecting the microfoundations of space while providing an accurate spatialization, crucial aspects to create knowledge useful for decision-making. Hence, the paper showcases spatial models tailored to address the differences in Spatial Attractiveness, based in spatial and economic territorial exposure indexes, to unveil the territorial-imbalances’ spatial logics. Organized in a GIS-based environment and using Tuscany as a proof-of-concept, the index-models identified factors of sensitivity or support to firms placed within industrial agglomerates providing an overview of spatial attractiveness within the territory, useful for supporting decision-making practices.